Immune Reactions Against Elongation Factor 2 Kinase: Specific Pathogenesis of Gastric Ulcer from Helicobacter pylori Infection - Kiyoshi Ayada; Kenji Yokota; Yoshiro Kawahara; Yumiko Yamamoto; Kazuyuki Hirai; Tomoki Inaba; Masahide Kita; Hiroyuki Okada; Kazuhide Yamamoto; Keiji Oguma (Clinical and Developmental Immunology)
Helicobacter pylori (H. pylori) infection is a definite causative factor for gastric ulcers (GUs). In the present study we detected a specific antigen of gastric epithelial cells (HGC-27) using cell ELISA, which was recognized by the sera of GU patients (n=20) but not in patients with chronic gastritis (CG; n=20) or in healthy volunteers (HC; n=10). This antigen was over-expressed by a stressful (heat-stressed) environment, and was identified as elongation factor 2 kinase (EF-2K) by western blotting. The GU patients' lymphocytes stimulated by H. pylori specifically disrupted heat-stressed HGC-27 cells in a cytotoxic assay. In flow cytometry, the effector cells (lymphocytes) from GU patients were significantly differentiated to T helper type 1 lymphocyte (Th1) and cytotoxic T lymphocyte (CTL) as opposed to those from CG patients. The target cells (HGC-27) expressed EF-2K and MHC-class I together with costimulatory molecules from heat stress. This antigen specific immune mechanism could have a prominent role in the pathogenesis of GU.